Information accessibility for students with disabilities: An exploratory study of Pakistan - Awais, Sania; Ameen, Kanwal; Awais, Sania; Ameen, Kanwal (Malaysian Journal of Library and Information Science, 2017)
Awais, S., & Ameen, K. (2015). Information accessibility for students with disabilities: An exploratory study of Pakistan. Malaysian Journal of Library & Information science, Vol.20, no. 2: 103-115. Pakistan is signatory to the ‘Convention on the Right of Person with Disabilities’ which reiterates upon equal right of information accessibility. This exploratory study is aimed to investigate the actual situation of information accessibility for students with disabilities (SWDs) in Lahore city of Pakistan. It involves qualitative data gathering techniques using interviews involving six SWDs and reality verifying observations of their school and college library services. Findings indicate that: (a) SWDs rely on only family members and teachers for support in accessing information; (b) both schools and colleges’ library services hardly provide required information services to the SWDs. Desired steps have been recommended to enhance information accessibility for SWDs. It is recommended that SWDs be provided with a library is located at accessible places, and equipped with trained staff, as well as reading materials in suitable alternative formats. This study is an effort for generating awareness among all stakeholders providing SWDs for equal information accessibility, such as the government, non-governmental organizations, educational institutions and Library and Information Science (LIS) professionals not only in Pakistan but also in other South Asia countries experiencing similar conditions of equality issues in information services.